Who defends democracy and why? Explaining the participation in the 2016–2017 candlelight protest in South Korea. Issue 3 (3rd April 2021) - Cho, Young Ho; Hwang, Injeong
ABSTRACT: Who defends democracy? This is a question central to the literature on democratic development, and a new generation of scholars has integrated structural- and actor-centric approaches to democratization to produce generalizable insights. However, their theoretical arguments lack sufficient empirical evidence from non-Western countries. From late October 2016 to April 2017, seven million Koreans (14% of the population) raised candles and participated in anti-government rallies, which eventually halted the deconsolidation of Korean democracy. The candlelight protest is a useful case for testing the expectations of these actor-centric theories. Analysing the latest World Values Survey, this study finds that many of the protest participants were young and attentive middle-class citizens and opposition party supporters in the capital areas. Their motivations were democratically defensive and reformative rather than transformative and postmodern but differed across economic classes. These results shed fresh light on these actor-centric theories of democratization and make significant implications regarding new democracies.